Increased serum YKL-40 level is associated with the presence and severity of metabolic syndrome - Akboğa, Mehmet Kadri (Anatol J Cardiol, 2016)
OBJECTIVE: Metabolic syndrome (MS) is defined by a cluster of interdependent physiological, biochemical, and clinical risk factors and linked to a state of chronic inflammation. YKL-40 is known as an inflammatory glycoprotein, which is secreted by various cell lines during inflammation. Thus, we aimed to assess the association of serum YKL-40 levels with the presence and severity of MS. METHODS: In this prospective cross-sectional study, a total of 177 consecutive patients [n=114 MS present and n=63 MS absent] were enrolled. MS was defined according to National Cholesterol Education Program Adult Treatment Panel III (NCEP-ATP III) criteria. Serum YKL-40 and hs-CRP levels were measured for all participants. RESULTS: Serum YKL-40, hs-CRP and white blood cell count (WBC) were significantly higher in the MS present group (p<0.05). There was a graded relationship between increasing number of MS components and serum YKL-40 level (p<0.05). In addition, serum YKL-40 level was positively correlated with hs-CRP level (r=0.467, p<0.001) and WBC count (r=0.251, p=0.001). In multivariable regression analysis, serum YKL-40 [1.022 (1.011–1.033), p<0.001] and hs-CRP [1.346 (1.111–1.632), p=0.002] were remained as independent predictors for the presence of MS. In the ROC curve analysis, using a cut-off level of 147.0, YKL-40 well predicted the presence of MS with a sensitivity of 73.7% and specificity of 69.8% (AUC: 0.785; 95% CI: 0.718–0.853, p<0.001). CONCLUSION: In this study, we demonstrated that serum YKL-40 level was significantly associated with the presence of MS. According to these findings, we concluded that serum YKL-40 may be a novel and useful indicator for MS. (Anatol J Cardiol 2016; 16: 953-8)